The Development of Teaching Material for Blended Learning: A Strategy to Improve Students’ Creativity and Innovation in the 21st Century - Pattaufi Pattaufi; Dedy Aswan; Abdul Hakim (Universitas Negeri Makassar, 2023)
The study aims to develop a blended learning design to optimize the Microteaching subject in the Educational Technology program. The development method implemented here was the Integrative Learning Design Framework (ILDF), which consists of three stages: exploration, formulation, and evaluation. We used the PEDATI model to design synchronous and asynchronous learning activities in the formulation process. The research outcome is a prototype of blended learning material for microteaching subjects integrating face-to-face and online learning. Validation by an expert in media, learning design, and material shows that it is in a good category. Besides that, the N-gain score of 0.7 indicated that the 21st-century skills students must possess include teaching creativity that can be learned through blended learning. A proper learning model supports an effective and efficient learning process. The research findings can be used to design blended learning design in the future to create a more innovative and interactive learning process.